Forensic Footwear Comparison: Leveraging AI Tools for Enhanced Analysis - Rashi Verma; Vinny Sharma; Ranjeet Kr. Singh; Manjeet Kumar (Indian Journal of Forensic Medicine and Pathology, 2025)
Footwear impressions serve as a crucial type of evidence in forensic investigations, effectively linking suspects to crime scenes with remarkable accuracy. This research explores the efficacy of three widely utilized casting materials - Plaster of Paris, Latex Rubber, and Dental Stone when applied to various soil types. Additionally, the study examines the impact of artificial intelligence (AI) in enhancing the analysis of these impressions. The main objectives were to investigate footwear impressions differ across diverse surfaces, identify which casting material captures the most precise details, and evaluate whether AI tools can provide more dependable comparisons than traditional visual inspection. Digital images of both the original and cast impressions were analyzed using an AI algorithm that included grayscale conversion and histogram analysis. Statistical technique chi-square tests, indicated significant differences based on the type of surface and material used. The findings revealed that original impressions exhibited superior clarity and detail compared to cast impressions. This study highlights the necessity of careful material selection and the incorporation of AI to enhance accuracy and reliability in the forensic examination of footwear impressions.